Morphological patterns of balanoposthitis and their correlation with final etiological diagnosis - Manish Jain; Farzana Ansari; Nidheesh Agarwal; Asit K Mittal (Wolters Kluwer Medknow Publications, 2023)
Background: Balanoposthitis is a common dermatological condition across the globe, but studies describing clinico-morphologic features and their diagnostic correlates are scarce. Objective: To study various morphological patterns of balanoposthitis and their correlation with etiological diagnosis. Materials and Methods: A cross-sectional study was conducted on all patients with balanoposthitis visiting the dermatology out-patient department and sexually transmitted disease (STD) clinic over a period of 8 months. Detailed history, demographic data, and clinical features were recorded. Relevant investigations were performed. Results: A total of 129 patients of balanoposthitis were studied. Common causes were because of candida (33.3%), bacteria (17.1%), irritants (13.3%), herpes (11.4%), drugs (8.6%), and lichen sclerosus (6.7%). Common morphological patterns were erosion/confluent wet erythema with sub-preputial discharge (24.81%), fissure with superficial pustules (15.5%), fissure alone (13.18%), patchy dry erythema (11.63%), and superficial pustules (intact or exfoliated) with or without underlying erythema (10.85%). Fissure and superficial pustules were the most common presentation of candidal balanoposthitis (51.43%), erosions/confluent wet erythema with sub-preputial discharge of bacterial balanitis (55.56%), and patchy dry erythema of irritant balanitis (50%). Limitations: Detailed investigations such as fungal culture, herpes serology, real-time polymerase chain reaction and histopathology could not be performed. Conclusion: Certain morphological patterns of balanoposthitis strongly point toward final diagnosis which can help in quick diagnosis and early treatment in resource poor settings, especially in STDs.